Efficient Optical Trapping and Detection of Nanoparticle Via Plasmonic Bowtie Notch - Yi-Chang Lin; Po-Tsung Lee (IEEE Photonics Journal)
For manipulating nanoparticles, we propose a nanotweezer named plasmonic bowtie notch (PBN) by adding a thin metal film to the bottom of plasmonic bowtie aperture. The PBN can exert a large trapping force on nanoparticle because the enhanced field of resonance mode can be much accessed by nanoparticle. The optical properties and factors influencing trapping force of PBN are fully investigated and discussed. The optimized PBN shows an excellent trapping capability with ultralow threshold excitation intensity of 0.64 mW/μm2 for stable trapping of a 100 nm polystyrene particle. In addition, it provides a label-free detection of the trapped particle by observing the extinction spectrum. The sensitivity to trapped target size of 71 pm redshift in peak wavelength per 1 nm increase of particle size is relatively high compared with those obtained from most near-field tweezers. Furthermore, the footprint of PBN is only 200 nm × 220 nm. The capabilities of the proposed design show a great potential in the application of nanoparticle trapping and sensing.